Optimal power peak shaving using hydropower to complement wind and solar power uncertainty. (1st April 2020) - Liu, Benxi; Lund, Jay R.; Liao, Shengli; Jin, Xiaoyu; Liu, Lingjun; Cheng, Chuntian
Highlights: A day-ahead hybrid hydro-wind-solar coordinated peaking operation model is proposed. Use non-parametric kernel density estimation to describe new energy forecast error. The model is recast as a successive linear programming problem. Multi case studies examine the effectiveness and applicability of the model. Abstract: Booming renewable energy development, such as wind and solar power, with their intermittency and uncertainty characteristics, pose challenges for power grid dispatching, especially for power grid peak shaving. In this paper, coordinated operation of hydropower and renewable energy in a provincial power grid is explored to alleviate fluctuation and aid peak shaving. Considering their aggregate effect, this study aggregates wind power plants and solar power plants into a virtual wind power plant and a virtual solar power plant, respectively, and the forecasted error distribution of wind and solar power is analyzed with kernel density estimation. Then, based on the principles of using hydropower to compensate for fluctuating wind and solar power, a day ahead peak shaving model with the objective of minimizing residual load peak-valley difference is built, which introduces chance constraints for forecast errors and coordinate hydropower operation with wind and solar power. To simplify the solution, the proposed model is recast as a successive linear programming problem. Day-ahead scheduling case studies of a provincial power grid system indicate that the proposed model can conduct peak shaving effectively, hydropower can compensate wind and solar power fluctuation, improve the stability of combined output, and make better use of renewable energy. Therefore, this study provides an alternative approach for peak shaving operation of power system with hydropower and increasing integration of wind and solar power in China and other places worldwide.